Whale Fall Ecosystems- An Unknown Deep Sea Ecosystem - Sahu, Ashish; Sahadevan, Pramila; Singh, Mahender (Chronicle of Bioresource Management, 2023)
In nature, every death brings new life. A fascinating example is the whale fall ecosystem. When a whale dies, its carcass will sink down to the seafloor where it creates a unique ecosystem for bottom-dwelling organisms. In short, a whale fall is a food boon in this typically nutrient-poor region of the ocean and use up everything they can, until the last vertebra is decompose. Four stages of ecological succession in a whale-fall include mobile-scavenger stage, enrichment-opportunist stage, self-fulfilling stage and reef stage. Whale carcasses become hotspots for ocean life, which supports more than 400 animal species. Over 120 new species have been discovered living at whale falls including, Osedax frankpressi, polychaete worms (zombie worm and bone-eating worm), which were first discovered living on the bones of a gray whale in 2002. Carbon sequestration through whale falls, or carcasses is substantial. More than 1,45,000 tonnes of carbon are transferred to the ocean floor by the dead bodies of whales each year. These so called whale fall also greatly enhance the diversity of the deep-sea ecosystem.